The effect of exchange rate and palm oil prices towards export earning of palm oil industry in Indonesia / Sazeera Jafrahim - Jafrahim, Sazeera (2008)
This study was examined the effect of exchange rate and palm oil price towards exports earning of palm oil industry in Indonesia. Exchange rate and palm oil price, both are important to study the effects of exports earning in palm oil industry. The study was used detailed monthly data for the past 11 years, from 1996 to 2006. An issue of current interest is to know whether exchange rate and palm oil price can influence the exports earning in Indonesia palm oil industry. The paper has been used multiple linear regression method to see the relationship between dependent and independent variables. Exports value was used as dependent variable while currency exchange rate, crude palm oil price, and crude kernel palm oil price were used as independent variables. According to the analysis for the year 1996 to 2006, which based on multiple linear regression found that, Crude Palm Oil (CPO) price, Crude Palm Kernel Price(CPKO) and Exchange Rate (Rp/US) are significantly influence the export earning of palm oil industry in Indonesia. Al the independent variables also have a positive relationship with the export earning.